2015
DOI: 10.1007/s00114-015-1303-6
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol enhances the acquisition of lithium chloride-induced conditioned taste aversion in castrated male rats

Abstract: The present study examined the effects of short-term treatment with ovarian hormones on the acquisition of conditioned taste aversion (CTA). Adult male rats were castrated and randomly divided into LiCl- and saline-treated groups. Nineteen days after castration, all of the animals were subjected to 23.5-h daily water deprivation for seven successive days (day 1 to day 7). On the conditioning day (day 8), the rats received either a 4 ml/kg of 0.15 M LiCl or the same dose of saline injection immediately after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Circulating levels of estrogen have been found to influence conditioned disgust behaviors in rats, as evidenced by the rats' increased aversive responses to the reinforced context during the period of proestrus compared to diestrus 58 . It also has been reported that nausea, malaise, and conditioned aversive responses in animals are enhanced by estrogen 64 . Estradiol has been found not only to cause a shift in the palatability of a sucrose solution but also induce taste avoidance when paired with a novel sucrose taste 65 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Circulating levels of estrogen have been found to influence conditioned disgust behaviors in rats, as evidenced by the rats' increased aversive responses to the reinforced context during the period of proestrus compared to diestrus 58 . It also has been reported that nausea, malaise, and conditioned aversive responses in animals are enhanced by estrogen 64 . Estradiol has been found not only to cause a shift in the palatability of a sucrose solution but also induce taste avoidance when paired with a novel sucrose taste 65 .…”
Section: Discussionmentioning
confidence: 97%
“…58 It also has been reported that nausea, malaise, and conditioned aversive responses in animals are enhanced by estrogen. 64 Estradiol has been found not only to cause a shift in the palatability of a sucrose solution but also induce taste avoidance when paired with a novel sucrose taste. 65 These results indicate that susceptibility to malaise‐inducing agents in females is caused by endogenous levels of gonadal hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Results of prior studies have shown that estradiol can produce conditioned taste avoidance when paired with a novel sucrose solution, as well as conditioned aversion consisting of disgust responses to the sucrose taste . Estradiol has also been shown to enhance the acquisition of LiCl‐induced taste aversion in castrated male rats, possibly due to estradiol's illness inducing properties. In addition, the formation of conditioned taste aversion and reduction of food intake seen after administration of agonists for ERα, ERβ and GPER‐1 is likely associated with the nausea and potentially disgust related responses elicited by estrogens, .…”
Section: Neurobiology Of Disgust and Pathogen/toxin Avoidancementioning
confidence: 99%